IDENTIFIKASI TELUR CACING NEMATODA USUS PADA KUKU MURID SEKOLAH DASAR NEGERI 11 RANOMEETO - Askrening - askrening (Meditory : The Journal of Medical Laboratory, 2018)
Background: Humans are intestinal nematode hosts whose transmission occurs through soil or soil transmited helminthes, as a place of life and development of worm eggs and larvae before they are transmitted to the human body, especially in children who are used to playing or direct contact with the soil, allowing the nails of Nematode eggs to be exposed the intestine.Purpose: The aim of this study was to determine the presence of intestinal nematode worm eggs on Ranomeeto 11 elementary school students. Methode: The type of research used is descriptive research, which was conducted on 28 June - 2 July 2016. The sample in this study was taken by Simple Random Sampling. The data taken in the form of primary and secondary data with the research instrument is a checklist and examination results. Data analysis techniques and data presentation are descriptive and presented in the form of frequency distribution tables and narrated.Result: The results of research conducted on 37 nail samples of Ranomeeto 11 Elementary School students showed that there were 5 positive samples containing intestinal Nematode eggs which were 4 positive Ascaris lumbricoides (10.82%) and 1 positive Trichuris trichiura (2.70%) and 32 (86 , 48%) negative samples do not contain intestinal nematodes.Conclusion: The conclusion of this study is that there are 5 positive samples of intestinal Nematode worm eggs 13.51% and 32 negative samples 86.48% do not contain intestinal nematode worm eggs.